RETENTION PERIOD – THE IMPORTANT STAGE OF ORTHODONTIC TREATMENT (LITERATURE REVIEW) - K.A. Solovei; L.V. Smaglyuk (Український стоматологічний альманах)
Orthodontic treatment involves two major periods: the period of active orthodontic treatment and consolidation of the orthodontic treatment results (retention). Instability results of orthodontic treatment may lead to recurrence of malocclusion, resulting in retention phase (the period following the end of active treatment). It  is necessary to save all the new teeth positions. After the orthodontic treatment 18.9% in adults and 36.8% in children recurrence may be developed.